2019
DOI: 10.3847/1538-4357/aaef8f
|View full text |Cite
|
Sign up to set email alerts
|

BAT AGN Spectroscopic Survey. XI. The Covering Factor of Dust and Gas in Swift/BAT Active Galactic Nuclei

Abstract: We quantify the luminosity contribution of active galactic nuclei (AGN) to the 12 µm, mid-infrared (MIR; 5-38 µm), and the total IR (5-1000 µm) emission in the local AGN detected in the all-sky 70-month Swift/Burst Alert Telescope (BAT) ultra hard X-ray survey. We decompose the IR spectral energy distributions (SEDs) of 587 objects into AGN and starburst components using AGN torus and star-forming galaxy templates. This enables us to recover the AGN torus emission also for lowluminosity end, down to log(L 14−1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
129
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(144 citation statements)
references
References 143 publications
(171 reference statements)
13
129
2
Order By: Relevance
“…However, the covering factor observed in X-rays (Ichikawa et al 2019) is larger (f obs,X ) than our predictions for any L AGN , as shown in Fig. 10.…”
Section: Comparison With X-ray Observationscontrasting
confidence: 59%
See 3 more Smart Citations
“…However, the covering factor observed in X-rays (Ichikawa et al 2019) is larger (f obs,X ) than our predictions for any L AGN , as shown in Fig. 10.…”
Section: Comparison With X-ray Observationscontrasting
confidence: 59%
“…Here, we select 179 AGNs with M BH = 10 7.5 − 10 8.5 M ⊙ from the total of 587 objects in Ichikawa et al (2019). Figure 10 compares the observed data with the hybrid model (red solid line) and SN-driven turbulence model (red dashed line) with M BH = 10 8 M ⊙ , C * ,max = 10 −7 yr −1 , r in = 1 pc,τ = 10 and Σ g = Σ g,crtit ≃ 1.0 g cm −2 .…”
Section: Comparison With Infrared Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In smooth tori, it is therefore expected that the ratio between the infrared and X-ray luminosities would be systematically higher in type 1 AGNs where inner parts of the torus are more visible. In reality, however, the correlations are very similar among type 1 and type 2 AGNs (Gandhi et al 2009;Ichikawa et al 2012Ichikawa et al , 2017Ichikawa et al , 2019Asmus et al 2015;Kawamuro et al 2016a).…”
Section: Introductionmentioning
confidence: 95%